ANALISIS SEMIOTIK DALAM NASKAH DRAMA DIE PHYSIKER KARYA FRIEDRICH DÃœRRENMATT - MAISYAROH, (UNIVERSITAS NEGERI SURABAYA, 2016)
Semiotic comes from Greek “semeion” that means sign. The sign mentions an information which communicative, able to change the others else (stand for something else). Based on the theory above, statement of the problem is (1) what kind of form signs on play script of Die Physiker by Friedrich Dürrenmatt?, (2) What is the meaning of form signs on the play script of Die Physiker by Friedrich Dürrenmatt? Thus, the purpose of the study is (1) describe the form signs which appeared on the play script of Die Physiker by Friedrich Dürrenmatt, (2) describe the meaning of form signs on the play script of Die Physiker by Friedrich Dürrenmatt. The type of the research is qualitative descriptive and data is analyzed by read and take a note technique. The researcher uses first and second of trikotomi theory by Peirce to answer the statement of the problem. The research result shows the play script of Die Physiker by Friedrich Dürrenmatt has 1 qualisign, 2 topology icon, 1 indeks and 9 symbolic semiotics. Keyword: semiotic.